2001
DOI: 10.1074/jbc.m005933200
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Smad2 Homologue fromSchistosoma mansoni, a Transforming Growth Factor-β Signal Transducer

Abstract: Smad proteins are essential intracellular signal transducers of the transforming growth factor-␤ (TGF-␤) superfamily. The TGF-␤ superfamily signals through phosphorylation and activation of R-Smad proteins, receptor-regulated Smads, by heteromeric complexes of ligand-specific type I and type II serine/threonine kinase receptors. R-Smads receive a signal from the activated receptor complex and transmit it to the nucleus. A cDNA was isolated that encodes a 649-amino acid protein found to be homologous to members… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 48 publications
4
52
1
Order By: Relevance
“…The completion of the genome sequencing project for S. mansoni will provide valuable information regarding the presence or absence of additional TGF-␤-signaling components in schistosomes. Whereas our studies and those of others (13) suggest that SmRK1 signals through SmSmad2, there is also an interaction between SmRK1 and SmSmad1. When the two proteins were coexpressed in R1B cells, moderate increases in luciferase expression from the GCCG-Lux reporter plasmid were observed relative to SmSmad1 expressed alone.…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations
“…The completion of the genome sequencing project for S. mansoni will provide valuable information regarding the presence or absence of additional TGF-␤-signaling components in schistosomes. Whereas our studies and those of others (13) suggest that SmRK1 signals through SmSmad2, there is also an interaction between SmRK1 and SmSmad1. When the two proteins were coexpressed in R1B cells, moderate increases in luciferase expression from the GCCG-Lux reporter plasmid were observed relative to SmSmad1 expressed alone.…”
Section: Discussioncontrasting
confidence: 45%
“…The specificity of interaction between R-Smads and type I receptors is facilitated by specific structural motifs in each protein. The predominant domain in the R-Smad is a region of 17 amino acids referred to as the L3 loop (19), and both SmSmads are highly conserved in this region relative to their mammalian counterparts (12,13). A 9-amino acid segment in the kinase domain of type I receptors referred to as the L45 loop has been reported to define the signaling specificity of type I receptors for intracellular responses (16).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a heterologous expression system, SmTbR1 was shown to interact with human TbRII and to activate Smad2 signalling molecules in response to human TGF-b [14]. Two R-Smads (SmSmad1 and SmSmad2) as well as a Co-Smad (SmSmad4) have been identified as downstream partners of SmTbR1 [15][16][17]. The existence of a conserved TGF-b signalling pathway in S. mansoni was further confirmed by Knobloch et al [18] who demonstrated an Fig.…”
Section: Conserved Tgf-b Signalling In Parasitic Helminthssupporting
confidence: 49%